Analisis Kebutuhan Dan Penyediaan Energi Listrik Di Kota Pekanbaru Tahun 2015-2024 Dengan Menggunakan Perangkat Lunak LEAP - M Ridwan Gaffari; Nurhalim Nurhalim (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The estimation of power consumption within Pekanbaru area in the coming decades is being analyze using of the software Long-range Energy Alternative Plan Systems (LEAP). The calculation is done by putting some variables of electrical energy consumption and the grow of electric consumption. The result of LEAP analysis is showing the grow of power consumption during period of 2015-2024 by 9,63% per year or in the other word increasement from 1667,43% GWh into 3943,04% GWh. The government and electric company (PLN) need to put attention and effort to make sure the figure of grow are able to realize. The effort is indicated by localizing the potential of power generation to be build within the area of Riau Province. Those potential of power generator includes some renewable energy i.e Microhydro Power Plant, Solar Power Plant Centralized, Solar Street Lighting, and biomass/biogass plant. Some of typical resources can be considered such as water potential, coal potential, and peat potential.Keywords: Electricity, Intensity energy, LEAP, Renewable energy